Green synthesis, characterization and antibacterial activities of silver nanoparticles using Sida schimperiana Hochst. ex A. Rich (Chifrig) leaves extract - Wendmnew Moges; Yohannes Misskire (Discover Materials)
Abstract The use of metal nanoparticles as antibiotics for resistant pathogens has become a current topic of research. Biosynthesized nanoparticles are promising drugs as antibacterial agents by inhibiting bacteria from infectious diseases. This study aimed at the synthesis and characterization of silver nanoparticles (AgNPs) from AgNO3 solution and Sida schimperiana Hochst. ex A. Rich leaves extract. The synthesized AgNPs were characterized by Fourier Transform Infrared (FTIR), Ultraviolet–Visible (UV–Vis) and X-ray diffraction (XRD) spectroscopic techniques and evaluated for antibacterial activities against Gram-positive (Staphylococcus aureus and Staphylococcus epidermidis) and Gram-negative (Escherichia coli and Klebsiella Pneumonia) bacteria by the disc diffusion method. The result indicated an initial color change that was observed below 400 nm for the leaves extract and 429 nm for AgNPs in the UV–Vis band supporting the synthesis of silver nanoparticles. The FTIR peaks at 3447, 1638 and 1413 cm−1 predict the hydroxyl, carbonyl and unsaturated C–C bonds, respectively, in the plant leaves extract. The XRD analysis showed that the synthesized AgNPs were crystalline in nature and face-centered cubic (FCC) structure with an average particle size of 26.27 nm. Furthermore, the synthesized nanoparticles showed antimicrobial activity to both types of bacteria, more significant being on Gram-negative bacteria (E. coli). In conclusion, the leaves extract of Sida schimperiana Hochst. ex A. Rich plant contains bioactive molecules that are used in the reduction and stabilization of AgNPs as potential antibacterial agents.